Safety-seeking behaviours and functional impairment in excessive worry and Generalized Anxiety Disorder (GAD) - Aron Freyr Kristjánsson 1995- (2022)
Generalized Anxiety Disorder (GAD) is a chronic condition with substantial functional impairment and high comorbidity with other mental disorders. GAD is the only anxiety disorder that does not have behavioural avoidance in its diagnostic criteria. Despite that, research has shown that GAD patients engage in maladaptive avoidance and safety-seeking behaviours (SSB). This study aimed to examine functional impairment in relationship with excessive worry and SSB measured with the Worry Behaviours Inventory (WBI). Participants consisted of 145 university students in Iceland, who completed measures of general psychopathology, worry-related safety seeking behaviour, excessive worry, and functional impairment. Mediation analysis indicated that scores on the WBI mediated the relationship between general psychopathology and functional impairment. The independent samples t-test revealed that those categorized as high worriers had higher scores on average on all measures. This study adds knowledge to the scarce literature on the role of behaviours in GAD possibly providing information of how to improve treatment planning and treatment interventions to counteract the burden and impairment that GAD has on individuals.